Handbook of fractures - Elstrom, John A.; Virkus, Walter W.; Pankovich, Arsen (McGraw-Hill, Medical Pub. Division, 2006)
Handbook of Fractures is the ideal portable resource for health care professionals who need to manage patients with musculoskeletal problems. The book focuses on the diagnosis, treatment and management of complications associated with treating the simplest as well as the more complex fractures.